Community Based Protection UNHCR In Realizing Community Security, Rohingya Refugees in Malaysia 2018-2021 - MUNTU, Efraim William; SEBA, Roberto Octovianus Cornelis; WIBISONO, Indra Wisnu (International Journal of Environmental, Sustainability, and Social Science, 2024)
The Rohingya refugees face significant challenges in seeking protection and security, both in their country of origin and in the countries where they seek refuge. In this context, the Community-Based Protection approach, promoted by UNHCR (United Nations High Commissioner for Refugees) in Malaysia between 2018 and 2021, plays a crucial role in creating a protection system based on community involvement in the design and implementation of policies. This approach emphasizes the importance of community security, which relies on state structures and involving refugee communities in safeguarding their safety. From the perspective of Institutional Liberalism, the international system, driven by multilateral institutions like UNHCR, can play a key role in ensuring effective protection for refugees by facilitating cooperation between countries and other international actors. This study aims to analyze how the community-based and community security approach to the safety of Rohingya refugees can enhance their sense of security and trust within the larger system. It also explores the relationship between the theory of Institutional Liberalism and the policies implemented by UNHCR to protect this vulnerable group.